2020
DOI: 10.1002/sdtp.13996
|View full text |Cite
|
Sign up to set email alerts
|

55‐4: Novel Methodology for Reproducibility of OLED Lifetimes and Identification of Killer Impurities

Abstract: A new method to investigate the influence of vacuum chamber impurities on OLED lifetime is demonstrated. By combining deposition from a novel‐design crucible with in‐situ exposure to impurity sources, and by controlling the amount of water impinging, we show that the influence of water and impurities can be separately examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…D3 should have a higher water content but D3 has a lower luminance decrease than D4 for both driving conditions. This could be attributed as a good approximation of the maximum lifetime error caused by device variation [12]. So, it can be concluded that diffusion of water in the devices is not a dominant effect.…”
Section: P-116 / R Mac Ciarnáinmentioning
confidence: 77%
See 1 more Smart Citation
“…D3 should have a higher water content but D3 has a lower luminance decrease than D4 for both driving conditions. This could be attributed as a good approximation of the maximum lifetime error caused by device variation [12]. So, it can be concluded that diffusion of water in the devices is not a dominant effect.…”
Section: P-116 / R Mac Ciarnáinmentioning
confidence: 77%
“…The deposition time, rate and thickness of each OLED layer was precisely controlled by a computer program and associated sensor system. Individual layer deposition times for different device runs were kept constant to obtain less fluctuations in the device lifetime [12]. 1.…”
Section: Oled Deposition With Controlled H2o Partial Pressurementioning
confidence: 99%